Microencapsulated sodium selenite supplementation in dairy cows: effects on selenium status. (10th September 2013) - Grilli, E.; Gallo, A.; Fustini, M.; Fantinati, P.; Piva, A.
Abstract : The objective of this study was to compare the efficiency of transfer of selenium (Se) to plasma and milk from inorganic sodium selenite, either free or microencapsulated, and from selenized yeast in dairy cows. The study consisted of an in situ -nylon bags incubation, and in an in vivo experiment to compare the Se status of cows supplemented with either sodium selenite, microencapsulated sodium selenite, or Se yeast. Thirty dairy cows, divided in five groups, were fed the following diets: the control group (CTR) received a total mixed ration supplemented with sodium selenite in order to have 0.3 mg/kg DM of total Se; 0.3M and 0.5M groups received the same control diet supplemented with lipid microencapsulated sodium selenite to provide 0.3 and 0.5 mg/kg DM of total Se, respectively; 0.3Y and 0.5Y groups received selenized yeast to provide 0.3 and 0.5 mg/kg of total Se, respectively. Cows were fed the supplements for 56 days during which milk, blood, and fecal samples were collected weekly to conduct analysis of Se and glutathione peroxidase (GSH-px) activity. Se concentration in the nylon bags was assessed to 72%, 64%, and 40% of the initial value (time 0) after 4, 8, and 24 h of incubation, respectively. In vivo, cows supplemented with 0.3 mg/kg of microencapsulated Se had higher milk Se concentration compared to CTR. The increment was more pronounced at the highest inclusion rate (0.5 mg/kg, 0.5M group). GSH-px activity was not significantly affected by treatments. The results indicate that lipid microencapsulation has the potential to protect nutrients from complete rumen reduction and that Se from microencapsulated selenite is incorporated in milk more efficiently than the free form. Microencapsulated sodium selenite was shown to be comparable to Se-yeast in terms of availability and incorporation in milk when fed at 0.3 mg/kg DM, whereas the inclusion in the diet at 0.5 mg/kg DM resulted in higher plasma and milk concentrations than selenized yeast.